Preparation method and application of MXene-polyeutectic-based conductive elastomer

By combining MXene with polyeutectic-based conductive elastomer, an in-situ polymerization technology was used to prepare MXene-polyeutectic self-healing conductive elastomer, which solved the problem of insufficient conductivity and sensitivity of existing conductive polymer elastomers, and achieved efficient self-healing and excellent mechanical properties of conductive elastomers.

CN116515038BActive Publication Date: 2025-03-04XIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310506700.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-03-04
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The conductivity and sensitivity of existing conductive polymer elastomers need to be further improved and optimized, especially after bending, impacting, scratching and friction, it is difficult to quickly restore its mechanical properties, conductivity and sensitivity.

Method used

Using the preparation method of combining MXene with polyeutectic conductive elastomer, the in situ polymerizable carboxylic acid monomer and polymerizable amide monomer are mixed, Ti3AlC2, lithium fluoride and hydrochloric acid are added, and a single-layer Ti3C2Tx nanosheet aqueous solution is obtained after reaction and centrifugation, and then mixed with a photoinitiator and irradiated with ultraviolet light on the casting horizontal plate to achieve in situ polymerization, and MXene-polyeutectic self-healing conductive elastomer is prepared.

Benefits of technology

By introducing polyacrylamide, the viscoelasticity of the polymer is improved, and the conductivity and strain sensitivity are optimized through the unique layered structure of MXene, the higher room temperature self-repair efficiency and excellent mechanical properties of the conductive elastomer are achieved, and the electrical properties of the material are basically unchanged after multiple self-repairs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116515038B_ABST
    Figure CN116515038B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a MXene-poly eutectic-based conductive elastomer, comprising the following steps: preparing a clear, transparent, and performance-adjustable polymerizable eutectic solvent ternary system by a "one-pot method" by mixing a hydrogen bond acceptor choline chloride with a hydrogen bond donor acrylic acid and acrylamide; further adding a two-dimensional monolayer Ti3C2T x The nanosheets obtain a prepolymer solution of a multi-hydrogen bond network, and finally, under ultraviolet light initiation conditions, in-situ photopolymerization is performed to obtain a MXene / poly eutectic self-healing conductive elastomer. The preparation process of the present invention is simple, efficient, and green, and reduces the production cost of the material and the complexity of the process technology. The present invention improves the conductivity and strain sensitivity of the elastomer, enriches the hydrogen bond network composition in the conductive elastomer, and ensures the room temperature self-healing properties of the conductive elastomer. The conductive elastomer prepared by the present invention can be used for strain sensing detection for monitoring different human activities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible conductive polymer materials, and specifically relates to a method for preparing a MXene-poly eutectic-based conductive elastomer; and also relates to the application of the MXene-poly eutectic-based conductive elastomer prepared by the preparation method. Background Art

[0002] With the increasing demand for advanced flexible electronic devices, research on conductive polymer composite elastomer materials has become increasingly popular and has been widely used in environmental monitoring, healthcare, sensors, flexible electrodes, wearable electronics and other fields. However, in practical applications, operations such as bending, impact, scratching and friction will inevitably cause certain mechanical damage to flexible conductive materials, which may lead to a decrease in the electrical performance and service life of the device. Therefore, how to design the structure and composition of conductive polymer elastomers to ensure that they can quickly restore their mechanical properties, conductivity and sensitivity at room temperature after damage remains a challenge.

[0003] Deep eutectic solvents (DES) are a type of ionic liquid that have the characteristics of good non-volatility, good biocompatibility, simple preparation, low raw material cost, low toxicity and 100% atomic utilization. In particular, deep eutectic solvents are highly designable and can usually be combined in different ratios by selecting appropriate hydrogen bond donors and hydrogen bond acceptors, thereby regulating their physicochemical properties over a large range. Recently, the preparation and application of conductive elastomers based on DES have become increasingly popular. According to the different roles played by DES in the system, they can be divided into two categories: (1) Conductive elastomers in which DES is used as a solvent. For example, Hu Jun et al. utilized the difference in the distribution state of polymers in different solvents and exchanged DES with good solvents to strengthen the interaction between polymers, inducing the formation of a uniform and strong polymer network, thereby obtaining a physically cross-linked low-melting gel with excellent mechanical properties [Advanced Functional Materials, 2022, 32(41): 2206305]; Yao Xi and Ju Jie et al. cooperated to develop a new type of low-temperature resistant DES ion conductor with environmental and chemical stability. Using it as solvent, hydroxyethyl methacrylate as monomer, and polyethylene glycol diacrylate as cross-linker, DES gel was prepared. The gel still maintained good flexibility and conductivity at low temperatures [International Journal of Smart and Nano Materials, 2021, 12(3): 337-50]; Wang Zhiguo et al. successfully achieved the preparation of conductive elastomers from cellulose raw materials in the DES system through a "one-pot" preparation strategy, without the need for solvent replacement and product separation, which provided a new idea for constructing green nano-microcrystalline cellulose composite conductive elastomers with excellent performance and sensitive detection [Chemical Engineering Journal, 2023, 454: 140022]. (2) DES is a conductive elastomer that serves as a solvent and a polymerizable monomer.For example, He Minghui's research group used the unique properties of the binary components of choline chloride (ChCl) and acrylic acid (AA) to prepare PDES that can be in situ photopolymerized and explored its application in patternable flexible deformation sensors [Journal of Materials Chemistry C, 2017, 5(33): 8475-81; Chemistry of Materials, 2020, 32, 874-881; ACS Applied Materials & Interfaces, 2019, 10(33), 28027-28035]; Li Ren'ai et al. introduced maleic acid (MA) into ChCl-AA type PDES to prepare the AA-ChCl&MA-ChCl PDES system, and after rapid in situ photopolymerization, a self-healing transparent conductive elastomer with insensitivity to organic solvents was obtained [Journal of Materials Chemistry A, 2020, 8(10): 5056-61].

[0004] However, as a common hydrogen bond donor in DES, the thermoplastic polyacrylic acid material obtained by in-situ photopolymerization of hydrogen bond donor acrylic acid is relatively soft and has a sticky surface at room temperature, which limits its further application in flexible conductive elastomers. In addition, in the poly-eutectic-based conductive elastomer system, its conductivity is mainly restricted by the number of chloride ions that can migrate in the hydrogen bond acceptor choline chloride, so its ion conductivity and sensitivity still need to be improved. In summary, the conductivity and sensitivity of the current conductive polymer elastomer need to be further improved and optimized. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a MXene-polyeutectic-based conductive elastomer, which solves the problem in the prior art that the conductivity and sensitivity of the conductive polymer elastomer need to be further improved and optimized.

[0006] The technical solution adopted by the present invention is:

[0007] The preparation method of MXene-polyeutectic-based conductive elastomer is specifically carried out in the following steps:

[0008] Step 1: mixing choline chloride, a polymerizable carboxylic acid monomer and a polymerizable amide monomer in a molar ratio of 1:x:y to form a mixture, wherein x+y=3; heating the mixture at 60-70° C. and stirring for 15-30 minutes to obtain a solution A that can remain clear and transparent at room temperature;

[0009] Step 2: Ti 3 AlC 2, lithium fluoride and hydrochloric acid in a molar ratio of 1:0.05:0.5, react the mixture at 40-60°C for 48-72h, obtain a precipitate by centrifugation, and wash the precipitate with deionized water until the pH of the supernatant is constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; the multilayer Ti 3 C 2 T x The aqueous solution was treated with ultrasound and centrifugation to obtain the supernatant, which is a uniformly dispersed single layer of Ti 3 C 2 T x The nanosheet aqueous solution was filtered to determine the solid content of the system and diluted with water to obtain an 8-12 mg / mL MXene aqueous solution;

[0010] Step 3: Single layer Ti 3 C 2 T x The nanosheets and the photoinitiator are added to the clear transparent solution A obtained in step 1, and the prepolymer solution B is obtained after ultrasonic dispersion in an ice bath; wherein the amount of the photoinitiator added is 2-5wt% of the solution A, and the monolayer Ti 3 C 2 T x The content of nanosheets is 0.2 to 0.8 g / L of prepolymer solution B;

[0011] Step 4: cast the prepolymer solution B prepared in step 3 onto a horizontal plate, and perform in-situ polymerization under ultraviolet light to obtain a MXene-poly eutectic-based self-healing conductive elastomer.

[0012] The present invention is also characterized in that:

[0013] In step 1, the polymerizable carboxylic acid monomer is one or more of maleic acid, angelic acid, methacrylic acid, crotonic acid, tiglic acid and itaconic acid.

[0014] In step 1, the polymerizable amide monomer is one or more of methacrylamide, N-ethylacrylamide, N-phenylacrylamide, N-isopropylacrylamide and N-isopropylmethacrylamide.

[0015] In step 3, the photoinitiator is one or more of photoinitiator 2959, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone and 2-hydroxy-2-methyl-1-phenylacetone.

[0016] In step 3, the ultrasonic power of ultrasonic dispersion in the ice bath is controlled to be 250-350 W, and the ultrasonic time is controlled to be 10-20 min.

[0017] In step 2, the parameters of the ultrasonic treatment are controlled as follows: the ultrasonic time is controlled to be 0.5 to 1.5 h, the centrifugal speed is controlled to be 2000 to 4000 rpm, and the centrifugal time is controlled to be 0.5 to 1.0 h.

[0018] In step 4, the parameters of ultraviolet light irradiation are controlled as follows: the wavelength of ultraviolet light is 365nm, the power is 40-60W, the height of the ultraviolet lamp from the glass plate is 10-15cm, and the irradiation time is 20-40s.

[0019] The beneficial effects of the present invention are that the preparation method and application of the MXene-poly eutectic-based conductive elastomer of the present invention can not only serve as a hard segment to improve the viscoelasticity of the polypropylene-based polymer after UV photopolymerization by introducing polyacrylamide, but also enrich its hydrogen bond network, so that the conductive elastomer can achieve higher room temperature self-healing efficiency;

[0020] The two-dimensional transition metal carbide / nitride / carbonitride (MXene) used in the present invention has a unique layered structure, a large active surface area, excellent chemical stability and good electrical conductivity, and can optimize its conductive elastomer to achieve higher conductive properties and strain sensitivity; the materials used in the MXene / poly-low eutectic-based self-healing conductive elastomer prepared by the present invention are all common chemical materials, the raw materials are easy to obtain, and the preparation method is simple and fast; after the MXene / poly-low eutectic-based self-healing conductive elastomer prepared by the present invention undergoes multiple self-repairs, the electrical properties of the conductive elastomer remain basically unchanged; the MXene / poly-low eutectic-based self-healing conductive elastomer prepared by the present invention can be used to sense different human body movements. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a flow chart of the preparation of MXene / poly eutectic-based self-healing conductive elastomer in Examples 1-4 of the preparation method and application of MXene-poly eutectic-based conductive elastomer of the present invention;

[0022] Figure 2 The scanning electron microscope, X-ray diffraction, and X-ray photoelectron spectrum of MXene in Examples 1-8 of the preparation method and application of MXene-polyeutectic-based conductive elastomer of the present invention;

[0023] Figure 3 The infrared spectra of DES, PDES and some raw materials in the comparative example 1 of the preparation method and application of MXene-polyeutectic-based conductive elastomer of the present invention;

[0024] Figure 4 The PDES in Examples 1-8 and Comparative Examples 1-2 in the preparation method and application of the MXene-polyeutectic-based conductive elastomer of the present invention 1 / 2 -MXene 0.0-0.8 and PDES2 / 1 -MXene 0.0-0.8 Stress-strain curve of

[0025] Figure 5 A diagram showing the self-healing process of the MXene / poly-eutectic-based self-healing conductive elastomer in Example 4 of the preparation method and application of the MXene-poly-eutectic-based conductive elastomer of the present invention;

[0026] Figure 6 This is a graph showing the monitoring of human body movement process and strain sensing performance of the MXene / poly eutectic-based self-healing conductive elastomer in Example 4 of the preparation method and application of the MXene-poly eutectic-based conductive elastomer of the present invention. DETAILED DESCRIPTION

[0027] The preparation method and application of the MXene-poly eutectic-based conductive elastomer of the present invention are further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0028] As a new type of two-dimensional material, MXene has tunable surface chemical properties and excellent metallic conductivity, making it widely used in sensing, thermoelectric, dielectric, optoelectronic, electromagnetic shielding and supercapacitor fields. Therefore, it is crucial to design and develop MXene / ternary poly eutectic polymer conductive elastomers with adjustable viscoelastic properties by utilizing the rich chemical groups on the surface of MXene two-dimensional conductive fillers, which can not only ensure the process is simple and green, but also ensure that it has good mechanical properties, room temperature self-healing, conductivity and sensing sensitivity.

[0029] The preparation method and application of the MXene-poly eutectic-based conductive elastomer of the present invention are further described in detail below through examples.

[0030] Choline chloride (ChCl), acrylic acid (AA) and acrylamide (AM) were dried under vacuum at 60 °C for 2 h before the experiment.

[0031] Embodiment 1:

[0032] Polymerizable deep eutectic solvent DES 1 / 2 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:1:2, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES. 1 / 2 , the prepared DES 1 / 2 Store in a vacuum desiccator containing silica gel until use in the next step.

[0033] Single layer Ti 3 C 2 T x Preparation: Ti 3AlC 2 , lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0034] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.2g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0035] PDES 1 / 2 -MXene 0.2 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 1 / 2 -MXene 0.2 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0036] Embodiment 2:

[0037] Polymerizable deep eutectic solvent DES 1 / 2 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:1:2, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES. 1 / 2 , the prepared DES 1 / 2 Store in a vacuum desiccator containing silica gel until use in the next step.

[0038] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2, lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0039] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.4g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0040] PDES 1 / 2 -MXene 0.4 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 1 / 2 -MXene 0.4 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0041] Embodiment 3:

[0042] Polymerizable deep eutectic solvent DES 1 / 2 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:1:2, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES. 1 / 2 , the prepared DES 1 / 2 Store in a vacuum desiccator containing silica gel until use in the next step.

[0043] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2, lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0044] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.6g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0045] PDES 1 / 2 -MXene 0.6 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 1 / 2 -MXene 0.6 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0046] Embodiment 4:

[0047] Polymerizable deep eutectic solvent DES 1 / 2 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:1:2, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES. 1 / 2 , the prepared DES 1 / 2 Store in a vacuum desiccator containing silica gel until use in the next step.

[0048] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2, lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0049] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.8g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0050] PDES 1 / 2 -MXene 0.8 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 1 / 2 -MXene 0.8 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0051] Comparative Example 1:

[0052] Polymerizable deep eutectic solvent DES 1 / 2 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:1:2, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES. 1 / 2 , the prepared DES 1 / 2 Store in a vacuum desiccator containing silica gel until use in the next step.

[0053] Preparation of prepolymer solution: Add photoinitiator 2959 to the prepared clear and transparent solution, and obtain the prepolymer solution after ultrasonic dispersion. The amount of photoinitiator is 3wt% of the prepared solution, the ultrasonic power is 270W, and the ultrasonic time is 10min.

[0054] PDES 1 / 2 -MXene 0.0 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 1 / 2 -MXene 0.0 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0055] Embodiment 5:

[0056] Polymerizable deep eutectic solvent DES 2 / 1 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:2:1, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES 2 / 1 , the prepared DES 2 / 1 Store in a vacuum desiccator containing silica gel until use in the next step.

[0057] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2 , lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0058] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.2g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0059] PDES 2 / 1-MXene 0.2 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 2 / 1 -MXene 0.2 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0060] Embodiment 6:

[0061] Polymerizable deep eutectic solvent DES 2 / 1 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:2:1, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES 2 / 1 , the prepared DES 2 / 1 Store in a vacuum desiccator containing silica gel until use in the next step.

[0062] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2 , lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0063] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.4g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0064] PDES 2 / 1 -MXene 0.4Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 2 / 1 -MXene 0.4 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0065] Embodiment 7:

[0066] Polymerizable deep eutectic solvent DES 2 / 1 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:2:1, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES 2 / 1 , the prepared DES 2 / 1 Store in a vacuum desiccator containing silica gel until use in the next step.

[0067] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2 , lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0068] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear and transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.6g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0069] PDES 2 / 1 -MXene 0.6Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 2 / 1 -MXene 0.6 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0070] Embodiment 8:

[0071] Polymerizable deep eutectic solvent DES 2 / 1 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:2:1, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES 2 / 1 , the prepared DES 2 / 1 Store in a vacuum desiccator containing silica gel until use in the next step.

[0072] Single layer Ti 3 C 2 T x Preparation: Ti 3 AlC 2 , lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5 and added to a plastic bottle. The mixture was reacted at 40°C for 72 hours, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti 3 C 2 T x aqueous solution; subsequently, the multilayer Ti 3 C 2 T x The aqueous solution was ultrasonically treated for 0.5 h and then centrifuged at 3000 rpm for 0.5 h to obtain the supernatant, which was a uniformly dispersed monolayer Ti 3 C 2 T x The nanosheet (MXene) aqueous solution was filtered to determine the solid content of the system and diluted to obtain a 10 mg / mL MXene aqueous solution;

[0073] Preparation of prepolymer solution: MXene and photoinitiator 2959 were added to the prepared clear transparent solution, and the prepolymer solution was obtained after ultrasonic dispersion. The amount of photoinitiator was 3wt% of the prepared solution, the content of MXene was 0.8g / L of the prepolymer solution, the ultrasonic power was 270W, and the ultrasonic time was 10min.

[0074] PDES 2 / 1 -MXene 0.8Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 2 / 1 -MXene 0.8 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0075] Comparative Example 2:

[0076] Polymerizable deep eutectic solvent DES 2 / 1 Preparation: Choline chloride, acrylic acid, and acrylamide were mixed in a molar ratio of 1:2:1, and the mixture was heated and stirred at 65°C in a flat-bottomed flask for 15 minutes to obtain a uniform clear and transparent solution DES 2 / 1 , the prepared DES 2 / 1 Store in a vacuum desiccator containing silica gel until use in the next step.

[0077] Preparation of prepolymer solution: Add photoinitiator 2959 to the prepared clear and transparent solution, and obtain the prepolymer solution after ultrasonic dispersion. The amount of photoinitiator is 3wt% of the prepared solution, the ultrasonic power is 270W, and the ultrasonic time is 10min.

[0078] PDES 2 / 1 -MXene 0.0 Preparation: The prepared prepolymer solution is cast onto a clean and horizontal glass plate, and polymerized under ultraviolet light to obtain PDES. 2 / 1 -MXene 0.0 Among them, the wavelength of ultraviolet light is 365nm, the power is 40W, the height of ultraviolet lamp from the glass plate is 10cm, and the irradiation time is 1min;

[0079] Performance testing of MXene-polyeutectic-based self-healing conductive elastomers:

[0080] (1) Morphology characterization: The MXene surface was scanned using a field emission scanning electron microscope (SU8000, Hitachi) for morphological characterization.

[0081] (2) X-ray diffraction test: X-ray diffraction (XRD) was measured using an X-ray diffractometer (Rigaku SmartLab SE); the X-ray diffraction scanning range was 5°-80°, and the scanning speed was 5° / min.

[0082] (3) X-ray photoelectron spectroscopy: X-ray photoelectron spectroscopy (XPS) was measured using an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha);

[0083] (4) Infrared test: The infrared spectrum of the sample was tested using a Fourier transform infrared spectrometer (Thermo Scientific Nicolet iS20); the wave number scanning range was 600-4000cm -1 , set the resolution to 4cm -1 The test environment temperature is 25℃ and the relative humidity is 30% to 35%.

[0084] (5) Mechanical properties test: The mechanical properties of the film were tested using an AI-7000-NGD electronic universal testing machine (Gottwell (Dongguan) Co., Ltd.). The sample size was 40 × 10 mm. 2 The loading rate is 10 mm / min. The test environment temperature is 25°C and the relative humidity is 30% to 35%.

[0085] (6) Resistance-time signal measurement: In the experiment, an electrochemical workstation (CHI660E) was used to measure the electrical signal change of the conductive elastomer, and the it mode was selected for measurement. The test environment temperature was 25°C and the relative humidity was 30% to 35%.

[0086] (7) Optical image capture: Use a camera to capture an optical image of the conductive elastomer.

[0087] The prepared MXene was characterized by scanning electron microscopy, and the successful preparation of the single-layer MXene can be clearly observed ( Figure 2 a); as shown in the XRD diagram ( Figure 2 b), appears in Ti 3 AlC 2 The (104) peak at 39° in the matrix is 3 C 2 T x disappeared, indicating that the Al layer was successfully etched; XPS spectrum showed that Ti 3 C 2 T x The Ti, C, O, F and Cl elements exist in the nanosheets ( Figure 2 c) and C-Ti-F, C-Ti-Cl, C-Ti-OH and C-Ti-O bonds ( Figure 2 e), which is consistent with the formation of F, Cl, OH and O surface end groups. According to the results calculated from the XPS spectrum, n(Ti):n(F):n(Cl)=27.79%:10.60%:5.44%( Figure 2 c) and n(Ti-OH):n(Ti-O)=32.1%:32.7%( Figure 2 e), and the rule n(F)+n(Cl)+n(O)+n(OH)=2, determine Ti 3 C 2 Tx The chemical formula is Ti 3 C 2 F 1.144 Cl 0.587 (OH) 0.133 O 0.135 .

[0088] In order to prove that the DES in step 1 and the prepolymer solution in step 4 are formed by hydrogen bonding, Fourier transform infrared spectroscopy was used to characterize the DES without adding photoinitiator ( Figure 3 c), in the formation of a clear and transparent liquid ( Figure 3 a) after, located at 1673cm -1 and 1722cm -1 The characteristic peaks at belong to the stretching vibration peaks of C=O in the acrylic acid and acrylamide components, respectively, indicating that the carboxyl and amino groups in the DES system exist in the form of carboxylic acid and amide, respectively, rather than in the form of molten salts. Therefore, combined with the comprehensive analysis of the physical appearance and infrared characterization results, it can be proved that the low eutectic solvent is hydrogen-bonded, and will not induce polymerization of the monomers during the heating and stirring stage. The components form a clear and transparent liquid under the interaction of hydrogen bonds.

[0089] exist Figure 3 The d is 1722cm -1 The stretching vibration peak of the carbonyl group at is used as the reference peak, and it is found that after polymerization, the DES system ( Figure 3 b), at 1427cm -1 The stretching vibration peak of C=C at 949cm -1 The relative intensity of the bending vibration peak of the terminal double bond =CH at Figure 3 It can be seen from the figure that the stretching vibration peaks of the C=O of the carboxylic acid and amide groups in DES are red-shifted after UV curing, from 1673 cm -1 and 1722cm -1 Transferred to 1661cm -1 and 1705cm -1 This indicates that after the in-situ polymerization of DES, most of the double bonds in the acrylic acid and acrylamide components were polymerized. Combined with the infrared results, it can be proved that PDES is a polymer network composed of covalent bonds and non-covalent hydrogen bonds.

[0090] Through mechanical testing, the mechanical properties of the MXene / poly-eutectic self-healing conductive elastomer prepared by the present invention are shown in the following table:

[0091] Table 1 Mechanical properties of MXene / poly eutectic based self-healing conductive elastomers

[0092] Test items Stress(MPa) strain(%) Comparative Example 1 15.96 3.28 Example 1 11.20 42.07 Example 2 10.28 103.83 Example 3 6.02 309.03 Example 4 1.43 743.02 Comparative Example 2 9.07 6.47 Example 5 2.23 105.79 Example 6 1.01 257.33 Example 7 0.75 531.01 Example 8 0.26 592.79

[0093] The MXene / poly eutectic self-healing conductive elastomer prepared in the present invention exhibits good mechanical properties, as shown in Table 1. Figure 4 As shown in Table 1 and Figure 4 As shown in the figure, as the content of MXene dispersion increases, the strain of the conductive elastomer gradually increases and the stress gradually decreases. In addition, since MXene aqueous solution is added, the introduction of water will greatly dilute or destroy the hydrogen bonds between MXene molecules and PDES, causing the internal hydrogen bond network to be destroyed, resulting in a decrease in its mechanical properties. Figure 4 By comparing a and b, it can be found that the overall strength increases significantly when the amount of acrylamide added increases. Therefore, by changing the amount of MXene dispersion and acrylamide added, the strength (15.96-0.26MPa) and flexibility (3.28-743.02%) of the conductive elastomer can be adjusted within a suitable range.

[0094] The MXene / poly eutectic self-healing conductive elastomer prepared in the present invention also has excellent self-healing performance. The conductive elastomer prepared in Example 7 of the present invention is first cut with a blade ( Figure 5 After a), the sections can be quickly self-healed after being spliced ​​together ( Figure 5 b), the self-healed conductive elastomer will not break after applying a certain force ( Figure 5 c) and can recover after the force is removed. Figure 5 At the same time, in order to characterize the electrical self-healing properties of the conductive elastomer, the cut conductive elastomer ( Figure 5 d) is connected to a series circuit with a small light bulb. When the cross-section is touched, the small light bulb lights up quickly ( Figure 5 f), in order to accurately measure its electrical self-repair rate, the it mode of the electrochemical workstation was used for testing. After it was cut off, the current quickly became 0, and when the cross-section was contacted, it could recover to the original current state within 1.2 seconds at the fastest. After four cycles, it could still maintain electrical self-repair within 1.2 to 1.5 seconds ( Figure 5 e). In summary, it can be shown that the conductive elastomer has excellent self-healing properties.

[0095] In addition, the conductive elastomer prepared by the preparation method of the MXene / poly eutectic self-healing conductive elastomer of the present invention can better distinguish the different amplitudes of human body movements in terms of human body movement monitoring. Figure 6As shown in the figure, the conductive elastomer can detect the real-time electrical signal changes of finger bending (a), finger bending at different angles (b), wrist bending (c), and elbow bending (d) with the help of an electrochemical workstation. With the change of bending amplitude, the specific data of ΔR / R changes from 15 to 60 and then to 250, which has a very intuitive change and high sensitivity. At the same time, sensing tests and sensitivity calculations were carried out within the range of small deformation (0%-25%). The data showed that the resistance of the conductive elastomer increases linearly with the increase of strain ( Figure 6 e), the sensitivity (GF) has reached 4.53 ( Figure 6 f), and is very sensitive to the response within the strain range of 0-25%. Therefore, the conductive elastomer prepared by the present invention can realize the monitoring of different movement amplitudes of the human body, or provide new inspiration for the improvement of flexible electronic devices.

[0096] The above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a MXene-polyeutectic-based conductive elastomer, characterized in that: Follow the steps below: Step 1: mixing choline chloride, a polymerizable carboxylic acid monomer and a polymerizable amide monomer in a molar ratio of 1:x:y to form a mixture, wherein x+y=3; heating the mixture at 60-70° C. and stirring for 15-30 minutes to obtain a solution A that can remain clear and transparent at room temperature; Step 2: Ti3AlC2, lithium fluoride and hydrochloric acid were mixed in a molar ratio of 1:0.05:0.5, and the mixture was reacted at 40-60°C for 48-72h, and then a precipitate was obtained by centrifugation. The precipitate was washed with deionized water until the pH of the supernatant was constant to obtain a multilayer Ti3C2T x aqueous solution; the multilayer Ti3C2T x The aqueous solution was treated by ultrasound and centrifugation to obtain the supernatant, which is a uniformly dispersed single-layer Ti3C2T x The nanosheet aqueous solution was filtered to determine the solid content of the system and diluted with water to obtain an 8-12 mg / mL MXene aqueous solution; Step 3: Single layer Ti3C2T x The nanosheets and the photoinitiator are added to the clear transparent solution A obtained in step 1, and the prepolymer solution B is obtained after ultrasonic dispersion in an ice bath; wherein the amount of the photoinitiator added is 2-5wt% of the solution A, and the monolayer Ti3C2T x The content of nanosheets is 0.2~0.8g / L of prepolymer solution B; Step 4: Cast the prepolymer solution B prepared in step 3 on a horizontal plate, and perform in-situ polymerization under ultraviolet light to obtain a MXene-poly eutectic self-healing conductive elastomer; In step 1, the polymerizable carboxylic acid monomer is one or more of maleic acid, angelic acid, methacrylic acid, crotonic acid, tiglic acid, itaconic acid or acrylic acid; In step 1, the polymerizable amide monomer is one or more of methacrylamide, N-ethylacrylamide, N-phenylacrylamide, N-isopropylacrylamide, N-isopropylmethacrylamide or acrylamide; In step 3, the ultrasonic power of ultrasonic dispersion in the ice bath is controlled to be 250-350 W, and the ultrasonic time is controlled to be 10-20 min; In step 4, the parameters of ultraviolet light irradiation are controlled as follows: the wavelength of ultraviolet light is 365nm, the power is 40-60W, the height of the ultraviolet lamp from the glass plate is 10-15cm, and the irradiation time is 20-40s.

2. The method for preparing a MXene-polyeutectic-based conductive elastomer according to claim 1, characterized in that: In step 3, the photoinitiator is one or more of photoinitiator 2959, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenylpropanone.

3. The method for preparing a MXene-polyeutectic-based conductive elastomer according to claim 1, characterized in that: In step 2, the parameters of the ultrasonic treatment are controlled as follows: the ultrasonic time is controlled to be 0.5-1.5 h, the centrifugal speed is controlled to be 2000-4000 rpm, and the centrifugal time is controlled to be 0.5-1.0 h.

4. The method for preparing a MXene-polyeutectic-based conductive elastomer according to any one of claims 1 to 3, characterized in that: The MXene-polyeutectic-based conductive elastomer prepared by this method is used in flexible electronic devices.

Citation Information

Patent Citations

  • High-transparency self-repairing solid material as well as preparation method and application thereof

    CN112552446A